Causal Analysis of Resource Management Capacity, Economic Welfare, and the Effectiveness of the Integrated Area Development Program: A Study in the Pesawaran Forest Management Unit, Lampung Province - Wulandari, Christine; Budiono, Pitojo; Kheynad; Haris, Achmad; Iwais, Niken Aurora; Vernanda, Aldina Refa; Alfarizi, Aditiya; Syafira, Hanna; Apriliani, Adella Putri; Sari, Fadela Yunika; Iskandar (Jurnal Sylva Lestari, 2026)
Sustainable rural development faces significant challenges due to climate change, land degradation, and economic pressures, particularly in regions heavily reliant on agriculture. Integrated area development (IAD) is one approach considered capable of integrating economic, social, and environmental aspects through agroforestry and strengthening local institutions. The IAD program is one part of the mainstreaming of the Social Forestry program of the Ministry of Forestry. However, empirical evidence regarding the specific role of community capacity in natural resource management as a mediator of IAD success remains limited. The purpose of this study is a quantitative causal analysis of the influence of economic welfare (X1) and natural resource management capacity (X2) on the success of IAD (Y1), as well as further research related to the mediating role of X2. Forty-two respondents were purposively selected for analysis using the SEM-PLS method, with natural resource management capacity and IAD success (Y1) as the main variables. The R-square value (0.618) and the goodness-of-fit (0.611) indicate that the research model is strong and relevant. Of the two existing hypotheses, all of them are proven significant; namely, increasing natural resource management capacity (X2) influences the success of IAD (Y1), and increasing community welfare (X1) influences increasing natural resource management capacity (X2) and also the success of IAD (Y1), where X2 is a mediating variable. This study argues that the policy for the success of IAD (Y1) in improving welfare must be explicitly implemented and directed toward strengthening community capacity for natural resource management. Keywords: agroforestry, community capacity, Integrated Area Development, KPH Pesawaran, SEM-PLS method